Research in Halal Health Tourism Development - Marlina, Lina (Journal of Islamic Economics Literatures, 2025)
Halal health tourism goes beyond individual medical treatments and encompasses a holistic environment that aligns with Islamic values, including a hospital environment consistent with Islamic ethics. This comprehensive offering becomes an important competitive factor among health tourism destinations. This study aims to examine the development of research on the topic of "Halal Health Tourism" and potential research plans based on journals published on this theme. This research uses a qualitative method with a bibliometric analysis approach. The data used is secondary data on the theme "Halal Health Tourism" from the Scopus database, with a total of 35 journal articles. The data was then processed and analyzed using the VosViewer application to map the bibliometric development of "Halal Health Tourism" research worldwide. The results of the study found 4 clusters with the most frequently used words being tourism, service, tourist, value, health, and medical tourism. Then, the research path topics related to Halal Health Tourism are Halal Health Industry Development, Pandemic Challenges in Halal Health Tourism, Muslim Patient Satisfaction in Halal Healthcare, and Trust and Risk in Halal Health Tourism.